Recollection of Bupleurum plantaginifolium (Apiaceae)—a threatened endemic species from the Nilgiris of the Western Ghats, India - Kanhirampadam, Prasanth Malamal; Chappan, Rekha; Madhavan, Manudev Kambiyelummal (Phytotaxa, 2025)
Bupleurum plantaginifolium, an endemic and threatened species of southern Western Ghats was recollected from its type locality of Elk hills of Nilgiri Biosphere Reserve, Tamil Nadu. A detailed description, photographs, distribution map and taxonomic notes are provided along with a taxonomic key to the species of genus Bupleurum distributed in the Western Ghats.